The Governance Slack Model: A cash flow approach for the budgeting and accountability of some corporate governance issues - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2002)
This paper introduces a cash flow model to budget and monitor distinctive matters usually arising in corporate governance. By enlarging the standard cash flow model widely used in Finance, and avoiding some of its downsides, it sets up a composite of cash flows called governance slack, which amounts to a comprehensive budget for the most usual governance issues. This slack has a dual structure whose dynamics keeps track of uses and sources of its components, preventing likely agency problems and improving not only disclosure but accountability as well.
Keywords: G30; G32; G38; 330; corporate governance; cash flow model; governance slack; cash flows budget